Jonah and the meaning of our lives : a verse-by-verse contemporary commentary - Bob, Steven M., 1950- (Jewish Publication Society ; University of Nebraska Press, 2016)
"The Book of Jonah stands unique among the biblical books of the prophets because it is almost entirely narrative. And, in contrast to all the other prophets portrayed as admirable individuals who bravely speak God's word, Jonah stands out as flawed and fleeing from God. We are drawn to Jonah because God gives him an opportunity to redeem himself. His experience inspires us to find our own second chances--and our own paths to meaningful growth."--Publisher's website.